2021
DOI: 10.1002/casp.2586
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between Instagram activity and female body concerns: The serial mediating role of appearance‐related comparisons and internalization of beauty norms

Abstract: Recent research showed that body image concerns (i.e., drive for thinness and body dissatisfaction) may be associated with exposure to images on social networking sites.We analysed this relationship by taking into account the possible mediating role of both the appearance-related comparisons (i.e., the comparison with others on a specific dimension) and the internalization of beauty standards (i.e., the acceptance of the predominant physical-attractiveness societal standards) in the Italian context. In two stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 58 publications
0
2
0
1
Order By: Relevance
“…This priming can be considered implicit, subconscious, and passive. In fact, a recent study shows that adolescents' social media use strongly influences their body concerns, and this pathway is mediated by the sequential mediation role of "appearance-related social comparison" and "internalization of aesthetic standards" [23] . Specifically, research on social comparison in social media has shown that the use of social media will initiate body comparison consciousness, and that the more comparative consciousness is primed, the more inclined one is to be aware of the differences between one's self and body image presented in media, leading to BID [4] .…”
Section: Why Is It So Common For Teenagers To Have Body Dissatisfacti...mentioning
confidence: 99%
“…This priming can be considered implicit, subconscious, and passive. In fact, a recent study shows that adolescents' social media use strongly influences their body concerns, and this pathway is mediated by the sequential mediation role of "appearance-related social comparison" and "internalization of aesthetic standards" [23] . Specifically, research on social comparison in social media has shown that the use of social media will initiate body comparison consciousness, and that the more comparative consciousness is primed, the more inclined one is to be aware of the differences between one's self and body image presented in media, leading to BID [4] .…”
Section: Why Is It So Common For Teenagers To Have Body Dissatisfacti...mentioning
confidence: 99%
“…Common sense yang dimaksud dalam lagu ini adalah body image positif terutama dalam hal mencintai diri sendiri. Penggalan lirik tersebut juga sekaligus mengkritik standar kecantikan yang dianggap tidak realistis karena body image didasarkan pada apa yang menjadi tren populer (Piccoli et al, 2022). Penyampaian pesan tersebut dikemas dengan komposisi yang sama dengan verse pertama.…”
Section: Intensi Penolakan Standar Kecantikanunclassified
“…Tutto ciò perché è lasciato spazio d'azione tra la creazione dei contenuti e la loro pubblicazione, consentendo agli utenti opere di editing. Non ci meraviglia affatto, dunque, che l'upload diffuso di foto che riproducono certi stereotipi di bellezza favorisca i processi di omologazione a determinati canoni, il che consente di interiorizzare il contenuto veicolato (Piccoli, Carnaghi, Grassi & Bianchi, 2021). L'essere letteralmente bombardati di immagini modificate, levigate e patinate, ci spinge a comportarci di conseguenza; in altre parole, si interiorizza la normatività veicolata (Chae, 2017).…”
Section: Corpi Online E Corporeità Onlife: Una Chance Educativaunclassified